2015
DOI: 10.1074/jbc.m114.631630
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Glutamate Residue in the C-terminal Deaminase Domain of Pentatricopeptide Repeat Proteins Is Required for RNA Editing Activity

Abstract: Background: Pentatricopeptide repeat (PPR) proteins that are required for RNA editing frequently include a C-terminal DYW deaminase domain. Results: Mutagenesis of a glutamate residue in the conserved deaminase HXE motif results in loss of editing activity. Conclusion:The glutamate residue is required for editing. Significance: The DYW deaminase domain of PPR proteins has the molecular characteristics of a deaminase.Many transcripts expressed from plant organelle genomes are modified by C-to-U RNA editing. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 52 publications
3
58
0
Order By: Relevance
“…() (top), and those proposed and used in this study (bottom). ‘PG’ indicates the conserved ‘PG box’ (Hayes et al ., ) while HSE and CxDC indicate the zinc‐binding deaminase signature sequence (Salone et al ., ; Hayes et al ., , ; Boussardon et al ., ; Wagoner et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…() (top), and those proposed and used in this study (bottom). ‘PG’ indicates the conserved ‘PG box’ (Hayes et al ., ) while HSE and CxDC indicate the zinc‐binding deaminase signature sequence (Salone et al ., ; Hayes et al ., , ; Boussardon et al ., ; Wagoner et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Cytidine deaminase is a Zn-dependent enzyme in which the CxxCH motif functions as a binding site [20]. The conserved His and Cys residues in the DYW domain combine with Zn ions, while the conserved Glu is required for deamination [8]. Thus, the DYW domain may be involved in nucleotide deaminations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hayes et al (2015) suggested that the conserved Glu residue of the HXE motif in the DYW domain is necessary for RNA editing. When the codon for the Glu residue in the DYW domain of OTP84 and CREF7 was mutagenized, the transgenic plants containing the mutated genes could not efficiently edit the cognate editing sites [8]. Wagoner et al (2015) proposed that the DYW domain and the E (or E+) domain are essential for cytidine deaminase activity because truncating either domain resulted in a QED1 protein that completely lacked any editing activity.…”
Section: Introductionmentioning
confidence: 99%
“…In phylogenetic distribution, the appearance of DYW domains in PPR proteins coincides with the appearance of RNA editing events. Moreover, mutagenesis of the conserved residues in DYW1, QED1, RARE1, OTP84 and CREF7 leads to loss of editing activity (Boussardon et al ., ; Hayes et al ., ; Wagoner et al ., ). However, the deaminase activity was not found by testing recombinant DYW proteins in vitro (Nakamura & Sugita, ; Okuda et al ., ).…”
Section: Introductionmentioning
confidence: 97%